2016
DOI: 10.1186/s13722-016-0057-6
|View full text |Cite
|
Sign up to set email alerts
|

Examining multi-session brief intervention for substance use in primary care: research methods of a randomized controlled trial

Abstract: BackgroundBrief interventions such as Screening, a single session of Brief Intervention, and Referral to Treatment (SBIRT) have shown mixed effectiveness in primary care. However, there are indications that multi-session brief interventions may demonstrate more consistently positive outcomes, and perhaps a more intensive approach would be of benefit in addressing substance use in primary care. This study compared the effectiveness of SBIRT with a single BI session (BI/RT) to a multi-session brief-treatment int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…Individual interventions designed to be used in a primary care setting such as Screening, Brief Intervention, and Referral to Treatment (SBIRT) programs are relatively straightforward to implement (Pfarrwaller et al, 2019). Evidence of the efficaciousness of SBIRT for substance use reduction, however, is mixed (Chambers et al, 2016), with some studies finding them effective (Aldridge et al, 2017; Bernstein, 2009) and others finding them ineffective (Haller et al, 2014; Kim et al, 2017). Motivational Interviewing (MI) and Motivational Enhancement Therapy are well suited to the primary care setting and have shown promise in helping youth reduce or abstain from marijuana use (Aldridge et al, 2017; D’Amico et al, 2018; Kells et al, 2019; Walker et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Individual interventions designed to be used in a primary care setting such as Screening, Brief Intervention, and Referral to Treatment (SBIRT) programs are relatively straightforward to implement (Pfarrwaller et al, 2019). Evidence of the efficaciousness of SBIRT for substance use reduction, however, is mixed (Chambers et al, 2016), with some studies finding them effective (Aldridge et al, 2017; Bernstein, 2009) and others finding them ineffective (Haller et al, 2014; Kim et al, 2017). Motivational Interviewing (MI) and Motivational Enhancement Therapy are well suited to the primary care setting and have shown promise in helping youth reduce or abstain from marijuana use (Aldridge et al, 2017; D’Amico et al, 2018; Kells et al, 2019; Walker et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…A brief motivational interviewing intervention was enacted by the BHCs to explore patient readiness to consider sobriety and explore what supports might be needed to make HCV treatment an attainable goal. 14 In other cases, a brief problem solving intervention may be needed to address obstacles to medication adherence and modifications of their daily routine, such as matching up medication times with a meal time or using an automated cell phone reminder. Further assistance was provided throughout the patient’s course of treatment to promote adherence and engagement, as requested by the primary care providers.…”
Section: Program Descriptionmentioning
confidence: 99%
“…Previous reviews suggested that, whereas content and settings of brief intervention did not influence the outcome, the practitioner group and age group of the population moderated the effect [15,30]. There is contradictory evidence of efficacy of BI being moderated by the number of sessions [4,15]. None of these reviews focussed mainly on the LMIC countries.…”
Section: Introductionmentioning
confidence: 99%